2021
DOI: 10.1038/s41598-021-87671-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel assessment considering spatial and temporal variations of water quality to identify pollution sources in urban rivers

Abstract: It’s vital to explore critical indicators when identifying potential pollution sources of urban rivers. However, the variations of urban river water qualities following temporal and spatial disturbances were highly local-dependent, further complicating the understanding of pollution emission laws. In order to understand the successional trajectory of water qualities of urban rivers and the underlying mechanisms controlling these dynamics at local scale, we collected daily monitoring data for 17 physical and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…The majority of the large world rivers are polluted by anthropogenic activities such as non degradable agriculture fertilizers and untreated industrial sewage discharge into rivers 13 . The river water quality is also declined gradually through toxic materials and excess nutrients supply from agrarian fields 14 . CPCB 15 reported that around 38,000 million liters per day untreated sewage and wastewater are discharged into the Indian River systems.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the large world rivers are polluted by anthropogenic activities such as non degradable agriculture fertilizers and untreated industrial sewage discharge into rivers 13 . The river water quality is also declined gradually through toxic materials and excess nutrients supply from agrarian fields 14 . CPCB 15 reported that around 38,000 million liters per day untreated sewage and wastewater are discharged into the Indian River systems.…”
Section: Introductionmentioning
confidence: 99%
“…The KWQI ranges from 0 to 100, with a higher value representing cleaner water. In this assessment, KWQI values were divided into the following ve grades: excellent (80-100), good (60-79), fair (40-59), poor (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and very poor (0-19).…”
Section: Kwqimentioning
confidence: 99%
“…With increasing industrialization and urbanization worldwide, the management of rivers in metropolitan areas is becoming more important [18][19][20] . In the case of the Geumho River in South Korea, the upstream section is relatively clean while nonpoint pollution sources discharge into the river under certain rainfall conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Multiparametric spatial and temporal study of water quality Nanfeihe River (China), conducted by the authors [Yang et al, 2021], indicates the need for careful selection of proper index to accurately trace the latent pollution sources of urban rivers. Thus, the City Water Quality Index is more informative than the Water Quality Index in determining potential pollution sources with heavy loads of pollutants.…”
Section: Introductionmentioning
confidence: 99%